STUDY ON PHYSICOCHEMICAL PARAMETERS AND PLANKTON COMPOSITION OF LAKE RIBADU IN FUFORE LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Inuwa, Emmanuel Hassan; Apagu, Abasiryu; Chaka, Bamaiyi; Mbilari, Mshelia B.; Mohammed, Musa; Filibus, Ngati (FUDMA Journal of Sciences, 2026)
This study assessed the physicochemical parameters and plankton composition of Lake Ribadu in Fufore Local Government Area of Adamawa State, Nigeria, to determine the influence of water quality on plankton distribution and its abundance. Water samples were collected monthly from three sampling stations (A, B, and C) between July and December 2025. Physicochemical parameters including temperature, turbidity, conductivity, dissolved oxygen (DO), biochemical oxygen demand (BOD), pH, total dissolved solids (TDS), and ammonia were analyzed using standard laboratory procedures. Plankton samples were collected using a 55 µm mesh net, preserved with Lugol’s iodine solution, and identified microscopically using standard identification keys. The Data was analyzed using one-way analysis of variance (ANOVA) to determine spatial variations among stations. The Results showed that temperature ranged from 22.00 to 29.04°C, turbidity from 38.00 to 66.00 cm, conductivity from 100 to 159 µS/cm, and dissolved oxygen from 3.7 to 6.6 mg/L. The pH ranged from 6.53 to 7.80, BOD from 5.0 to 7.6 mg/L, TDS from 100.60 to 106.86 mg/L, and ammonia from 0.03 to 0.08 mg/L. A total of 21 phytoplankton species belonging to four taxa (Bacillariophyceae, Chlorophyceae, Myxophyceae, and Chrysophyceae) with a total abundance of 433,677 cells/L were recorded. Bacillariophyceae was the dominant group (37.8%), followed by Chlorophyceae (35.12%), Myxophyceae (25.82%), and Chrysophyceae (1.53%). Zooplankton comprised 21 species (125,416 individuals/L), with Copepoda being most abundant (38.18%). The findings indicate that water quality conditions were within acceptable limits and supported diverse plankton communities, with seasonal variations influencing their distribution and abundance patterns.
Keywords: Physicochemical parameters; plankton composition; phytoplankton; zooplankton; water quality